Hiding in plain sight: the pursuit of war criminals from Nuremberg to the war on terror - Stover, Eric (University of California Press, 2016)
"Hiding in Plain Sight tells the story of the global effort to apprehend the world's most wanted fugitives. Beginning with the flight of an estimated thirty thousand Nazi war criminals after the Second World War, then moving on to the question of justice following the recent Balkan wars and the Rwandan genocide, and ending with the establishment of the International Criminal Court and America's pursuit of suspected terrorists in the aftermath of 9/11, the book explores the range of diplomatic and military strategies--both successful and unsuccessful--that states and international courts have adopted to pursue and capture war crimes suspects. It is a story fraught with broken promises, backroom politics, ethical dilemmas, and daring escapades--all in the name of international justice and human rights. In this exhaustively researched and compelling written work of political and judicial history, the authors argue that while the legal and operational regimes needed to apprehend and deliver suspected war criminals to justice are largely in place, the political will on the part of states to make arrests happen in a consistent and apolitical manner remains elusive. And until this situation is rectified, murderers will get away with murder, and torturers will retire with pensions"--Provided by publisher